Learning Strategies SD Muhammadiyah 2 Gempol During the Covid-19 Pandemic - Mochammad Lutfy Aziz; Muhlasin Amrullah (Proceedings of The ICECRS, 2021)
This scientific paper discusses several aspects, including: learning strategies at SD Muhammadiyah 2 Gempol. In the research process this time using descriptive qualitative research, data collection techniques used data collection techniques by means of direct interviews with the principal of SD Muhammadiyah 2 Gempol. This study aims to determine the changes in the learning system at SD Muhanmadiyah 2 Gempol and the learning strategies. In addition, the learning process must have a lot of challenges in implementing the programs that have been set by the school, especially in the current state of the covid-19 pandemic. Like many who are constrained by the current learning process, or other conditions. But even so, SD Muhammadiyah 2 Gempol continues to carry out the program and pays attention to the existing obstacles by utilizing technology for learning media in the school. Therefore, the learning process at SD Muhammadiyah 2 Gempol can continue to run even though there are several obstacles that can be solved with existing strategies.